2016
DOI: 10.7860/jcdr/2016/18197.8223
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal Fingerprints and BMI: Implications for Risk Factors in Dental Caries and Malocclusion

Abstract: IntrOductIOnMalocclusion is an appreciable deviation from the ideal occlusion and may be considered aesthetically unsatisfactory [1] thus implying a condition of imbalance in the relative sizes and position of teeth, facial bones and soft tissues (lips, cheek and tongue). Malocclusion is neither an unhealthy nor normal condition which occurs in most [2] as at this state the teeth stay firm, function efficiently, do not change the position during and after their contact, do not cause pain and remain in good st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
2
3
1
1
Order By: Relevance
“…The pooled results of 16 included studies showed that males had a slightly higher prevalence than females, which was consistent with the results reported in some previous studies but contradictory to the results reported in other studies . The differences in the prevalence between genders observed in this study may be attributed to the latest finding that the rates of obesity and overweight are greater for males than for females in China, and obesity has been shown to be a risk factor for malocclusion . In addition, the sexual dimorphism in skeletal maturity might have contributed to the variations in the reported results.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The pooled results of 16 included studies showed that males had a slightly higher prevalence than females, which was consistent with the results reported in some previous studies but contradictory to the results reported in other studies . The differences in the prevalence between genders observed in this study may be attributed to the latest finding that the rates of obesity and overweight are greater for males than for females in China, and obesity has been shown to be a risk factor for malocclusion . In addition, the sexual dimorphism in skeletal maturity might have contributed to the variations in the reported results.…”
Section: Discussionsupporting
confidence: 79%
“…14,47 The differences in the prevalence between genders observed in this study may be attributed to the latest finding that the rates of obesity and overweight are greater for males than for females in China, 48 and obesity F I G U R E 4 Forest plot of malocclusion in mixed dentition among different genders in mainland China during has been shown to be a risk factor for malocclusion. 49 In addition, the sexual dimorphism in skeletal maturity might have contributed to the variations in the reported results. Generally, pubertal growth spurts occur at 11.8 years of age in females and 13.8 years of age in males 50 ; therefore, females in the mixed dentition period are closer to their pubertal growth spurt than males.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, most of the participants had low 2D:4D ratio for both the hands. Similar results were shown by Priyanka GNDet al (2016) 4 where the authors' conducted the study to focus on the role of hormonal fingerprints in the early detection of malocclusion, caries, the influence of Body Mass Index (BMI) on caries and malocclusion along with identifying the association of BMI with 2D:4D ratio. Overall, 300 children from both sexes of age group 10 and 15 years were selected and digital vernier caliper was used for the measurements.…”
Section: Resultssupporting
confidence: 75%
“…These dissimilarities in the digit ratios are established by the 13th or 14th week of intrauterine life (second trimester) and exhibit substantial constancy over the lifetime. 4 This ratiotends to vary among different ethnic groups, and surprisingly,this variation is far larger than differences between the sexes as shown in the study conducted by Manning et alwhere in addition to the significant sexual dimorphism in 2D:4D, the mean ratios varied between the English, Scottish, Uygur, Han and Jamaican children. 5 Objectives Hence, this paper was undertakento study the correlation between 2D:4D ratio and dental caries and malocclusion prevalence inNorthern Province of Saudi Arabia, to identify caries and malocclusion prone individuals, so as to facilitate the prevention of these problems.…”
Section: Introductionmentioning
confidence: 71%
“…[ 8 ] Further research to inspect the impact of 2D:4D on caries with larger sample size is required to ascertain the relationship with hormonal fingerprints and practical application in dentistry. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%